Effects of Purple Rice and Morchella esculenta Powder Substitution on the Quality of Dough and Bread - Yuyue QIN; Hongda YU; Kejun CHEN; Guiguang CHENG; Jiliang ZHANG; Thanapop SOTEYOME (Shipin gongye ke-ji)
In order to meet people's demand for diversified and functional bread products, the effects of wheat flour substituted with purple rice (0, 3%, 6%, 9%, and 12%) and Morchella esculenta (0 and 3%) powder on the rheological behavior of dough, dietary fiber content, baking attributes of bread, starch digestibility in vitro, and volatile flavor compounds were investigated. The results indicated that the substitution of purple rice and Morchella esculenta powder enhanced the storage modulus and loss modulus of dough, while the \begin{document}$ tanδ $\end{document} value exhibited a gradual decline. Substitution of purple rice and Morchella esculenta powder elevated the dietary fiber content of bread, while decreasing the specific volume, elasticity, and cohesion of bread, and significantly (P<0.05) increasing the hardness and chewiness of bread. When the Morchella esculenta powder substitution content maintained was 3%, the content of purple rice powder was in the range from 0 to 12%, the L* value of bread crust and crumb gradually decreased and the ΔE value gradually increased, resulting in a darker color when compared to control group. The substitution of purple rice and Morchella esculenta powder decelerated the starch hydrolysis rate of bread. The electronic nose test revealed that the flavor substances were mainly alcohols, aromatics, aliphatic hydrocarbons, and esters, and the bread was rich in flavor. Therefore, the appropriate partial substitution with purple rice and Morchella esculenta powder could effectively improve the quality and characteristics of bread, and provided a useful reference for the development of functional bread.